Cultura afro-brasileira: resgate do repertório africano a reinvenção da cultura brasileira no espaço escolar - Santos, Mariana Amália dos [UNESP]; Stefanin, Thiago [UNESP]; Kobayashi, Maria do Carmo Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project aims to identify, describe and relate elements of african-Brazilian and African culture found in the Brazilian educational society. In fact the school space a distance was identified between the african-Brazilian culture and African culture, diagnosed students are unaware and not related to their cultural identity so this project is based awakening of these cultures. Analyze how the second experience (Dewey, 1979) worked through experiences in Art Education can add the cultural repertoire and identity of students in educational space.

O projeto tem como objetivo identificar, descrever e relacionar elementos da cultura afro-brasileira e africana encontrados na sociedade educacional brasileira. Na realidade do espaço escolar foi identificada uma distância entre a cultura afrobrasileira e a cultura africana, os alunos diagnosticados não tem conhecimento e nem relação com sua identidade cultural por isso esse projeto tem como fundamento o despertar dessas culturas. Analiso como a experiência segundo (DEWEY, 1979) trabalhada através de vivências em Arte Educação pode acrescentar o repertório cultural e na identidade dos alunos no espaço educacional.
Keywords: Culture; Art education; African-Brazilian; Cultura; Arte educação; Afro-brasileira